Coupling a single electron on superfluid helium to a superconducting resonator - Gerwin Koolstra (Nature Portfolio, 2019)
Electrons on the surface of helium have strong interactions with each other but weak coupling to dissipation mechanisms, providing opportunities for many-body physics and storing quantum information. Here the authors demonstrate a circuit QED platform for manipulating and probing few-electron clusters.